2020
DOI: 10.1016/s2214-109x(19)30464-4
|View full text |Cite
|
Sign up to set email alerts
|

Uncrewed aircraft systems versus motorcycles to deliver laboratory samples in west Africa: a comparative economic study

Abstract: Background Transportation of laboratory samples in low-income and middle-income countries is often constrained by poor road conditions, difficult geographical terrain, and insecurity. These constraints can lead to long turnaround times for laboratory diagnostic tests and hamper epidemic control or patient treatment efforts. Although uncrewed aircraft systems (UAS)-ie, drones-can mitigate some of these transportation constraints, their cost-effectiveness compared with land-based transportation systems is unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 8 publications
1
31
0
1
Order By: Relevance
“…Globally, we found exceptionally few scientific studies that reported on the economic perspective of drone technology in healthcare services [ 13 , 16 ]. This may be due to the slow-paced implementation of drone usage for medical purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, we found exceptionally few scientific studies that reported on the economic perspective of drone technology in healthcare services [ 13 , 16 ]. This may be due to the slow-paced implementation of drone usage for medical purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from expertise, infrastructure and regulations [ 14 , 15 ], one of the main barriers to surmount is the question of cost-effectiveness of drone usage. Thus far, there is only one study that attempted to answer the question of cost-effectiveness of drone for medical products transportation, the finding of which showed that motorcycles were more cost-effective than short-range (< 65 km) drones [ 16 ]. This result, however, may not be applicable in all types of geographical terrains or traffic.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the cost to utilize UAVs for routine transport of specimens is difficult considering the multiple assumptions that must be accounted for, including the type of UAV and the associated operational costs. A nationwide study in Liberia 12 determined that fully replacing the motorbike transport program with UAVs for lab samples would be more expensive to operate. Phillips et al 13 conducted a costing analysis that compared UAV-based systems to ground-based for the transport of laboratory samples from health facilities to labs in Malawi and found higher costs but lower travel times when using small, battery-powered UAVs for transport.…”
Section: Discussionmentioning
confidence: 99%
“…The same applied to the use of UAV within mass casualty incidents showing their feasibility. 35 36 Lastly in regard to medical transport, UAV have been successfully used to transport laboratory samples, 37 blood products, 38 39 vaccines 40 and flotation devices to prevent drowning. 41 The use of AED equipped UAV can therefore be seen as a reasonable extension of the previous applications.…”
Section: Open Accessmentioning
confidence: 99%